Effects of Ultrasound on the Removal of Humic Acids with the Preformed Aluminium Hydroxide Flocs - B. C. Qi (International Mineral Processing Congress, 2003)
"In water treatment, flocculation or coagulation with aluminium or ferric salts has been widely used for many years to remove natural organic matter (NOM), including humic acids. However, the adsorption of NOM to aluminium hydroxide flocs during conventional coagulation/flocculation processes is very complex, with the flocculation of aluminium hydroxide particles and the adsorption of NOM molecules on flocs occurring simultaneously. Any effect on the surface characteristics and micro-structures of the humic acids and aluminium hydroxides could affect the adsorption efficiency.It has been widely observed that if a reaction system (liquid-liquid or liquid-solid) is exposed to an ultrasound field, under appropriate conditions, a variety of physical (emulsification, aggregation/flocculation) or chemical (the production of radical and exited species; single electrotransfer) actions may be activated. Though the ultrasound effects have been used in biological and chemical decontamination in many conventional environmental protection practices, the idea to explore the ultrasound effects in the removal of humic acids by preformed aluminium hydroxide flocs is relatively new. In this paper, the effect of an in-situ ultrasonication on removal of the humic acids extracted from the acidification fermentation of lignocellulosic residues, by a preformed aluminium hydroxide, was evaluated; the effect of ultrasonication on the surface complexation of the humic acids with the preformed aluminium hydroxides was investigated."